If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -29 + a = -6(a + -1) Reorder the terms: -29 + a = -6(-1 + a) -29 + a = (-1 * -6 + a * -6) -29 + a = (6 + -6a) Solving -29 + a = 6 + -6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '6a' to each side of the equation. -29 + a + 6a = 6 + -6a + 6a Combine like terms: a + 6a = 7a -29 + 7a = 6 + -6a + 6a Combine like terms: -6a + 6a = 0 -29 + 7a = 6 + 0 -29 + 7a = 6 Add '29' to each side of the equation. -29 + 29 + 7a = 6 + 29 Combine like terms: -29 + 29 = 0 0 + 7a = 6 + 29 7a = 6 + 29 Combine like terms: 6 + 29 = 35 7a = 35 Divide each side by '7'. a = 5 Simplifying a = 5
| 13+6t=37 | | 2u=34 | | 3r+4r=-14 | | 13t+6t=37 | | r+4-3=4 | | 8(x+10)=8x+80 | | 5y+5=25 | | 2x+10=-8x-17 | | -1=1-5b+3 | | -15=3x+2x | | 5.9x+12=71 | | 7n+1=1 | | 400*x=300 | | 400*x=500 | | ln(2.5x)=8 | | x+12=(-8) | | 1+3p-2p=5 | | 11n^2-31n-14=n^2 | | 6f=-30 | | 8t-5m+3m-7t-(-3t)+m= | | 7n-5= | | 10=3n+2n | | x*.25=500 | | 2w^2-10w-40=0 | | 3k+1+3=1 | | 4(-9k+3)=3(12k+4)-3k | | -20=-7x+3(x-8) | | (3x^2)-32x+64=0 | | -4(-3+2)-3-(-4)=3+2 | | -4x-3x=7 | | n^2-6n-46=0 | | 5a-6-2=12 |